2017
DOI: 10.1002/2016gc006667
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity structure of the lithosphere‐asthenosphere boundary beneath the eastern North American margin

Abstract: Tectonic plate motion and mantle dynamics processes are heavily influenced by the characteristics of the lithosphere-asthenosphere boundary (LAB), yet this boundary remains enigmatic regarding its properties and geometry. The processes involved in rifting at passive margins result in substantial alteration of the lithosphere through the transition from continental to oceanic lithologies. Here we employ marine magnetotelluric (MT) data acquired along a 135 km long profile, offshore Martha's Vineyard, New Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Analysis of the Martha’s Vineyard MT profile for deep crustal and mantle structure using the full data bandwidth is presented in ref. 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the Martha’s Vineyard MT profile for deep crustal and mantle structure using the full data bandwidth is presented in ref. 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Note the ring of strong Δ V S 's around the outline of the NAA, especially on its seaward side (see section ). Attias et al's () lithospheric anomalous conductive zone (LACZ, blue line) is also shown.…”
Section: Estimates Of Lithospheric Thickness and Degree Of Heterogenementioning
confidence: 80%
“…Both effects would tend to increase the amplitude of S-to-P converted waves. Attias et al (2017) reports a 50-km-wide lithospheric anomalous conductive zone on the continental shelf south of Cape Cod, Massachusetts (Figure 4c), with electrical conductivities that are about 10 times higher than normal in the 40-to 100-km depth range. It is just south of one of the regions with negative velocity gradients and may represent a seaward extension that is out of range of the seismic imaging (which is based on stations on land).…”
Section: Shallow Lithospheric Heterogeneity Along the Seaward Edge Ofmentioning
confidence: 98%
“…Only limited electromagnetic surveys have been performed to image the electrical resistivity structure of passive margins. Authors have identified varying structures, such as a conductive lithospheric anomaly imaging mantle upwellings (Attias et al, 2017); upper-crustal conductors imaging subbasalt sediment basins (Hoversten et al, 2015), or graphite and massive sulfide mineralization (Corseri et al, 2017;Heinson et al, 2005); and high lower-crustal resistivities depicting magmatic underplating (Jegen et al, 2016). The underlying reason for the different characteristics is linked to the "plates vs. plumes" hypothesis, which discusses the triggers of continental breakup in terms of mantle convection, mantle plumes, melt generation, and plate tectonics (Anderson, 2001;Foulger, 2010;Morgan, 1971;Wilson, 1963).…”
Section: Introductionmentioning
confidence: 99%